Pendidikan Kesehatan Pada Anak Sekolah Dasar - Grouse Oematan; Utma Aspatria; Tasalina Gustam (GOTAVA, 2023)
Infectious disease is a disease caused by pathogenic microorganisms such as bacteria, viruses, fungi. The disease can be passed from person to person, through contact with contaminated surfaces or objects. One simple effort that can be done to help prevent infectious diseases caused by bacteria and parasites is to teach children about the importance of a clean and healthy lifestyle. Furthermore, to ensure that children want to change habits in a healthy direction, effort is needed, one of which is through education. Health education plays an important role in promoting the well-being and development of children in primary schools. The results of community service activities show an increase in students' knowledge after counseling is carried out.